Study Habits of Achievement Path Students Based on Choice of Graduation and Gender - Agung Satria Wijaya; Gina Fitri Anita; Neviyarni Neviyarni (Peneliti.net, 2023)
This study aims to analyze the study habits of achievement track students in attending lectures based on gender and choice of major. The research method used is descriptive and comparative. The study population was 157 Achievement Track students, with a sample of 61 students selected by proportional random sampling technique. The instrument used is a questionnaire of student study habits. Data were analyzed using the percentage technique and to see differences in student study habits in terms of gender, the t-test formula was used with the Independent Sample Test technique through the SPSS for windows release 20 statistical program. The research findings, in general: (1) student study habits are at pretty good category, (2) the study habits of students who passed the first and second choices were in the pretty good category, and the third choice was in the poor category, (3) the study habits of male students were in the pretty good category, (4 ) the study habits of female students are in the fairly good category, (5) there are significant differences in the study habits of students in terms of gender.